Optimizing airflow reversals for kiln drying of softwood timber by applying mathematical models - Pang, Shusheng (Maderas. Ciencia y Tecnología, 2014)
After experimental validation of a kiln-wide drying model, a single board drying model and a stress model for kiln drying of softwood timber, these models are integrated and used to investigate benefits of airflow reversals in smoothing moisture content distribution and in reducing drying stresses for commercial kiln drying. In the current study, a high temperature drying schedule (DB/WB of 120/70°C and air velocity of 5 m/s) was simulated and 5 strategies for airflow reversal were evaluated. These strategies are: airflow reversal every hour; airflow reversal every 2 hours; airflow reversal every 3 hours and airflow reversal after 2 and 10 hours of drying. The results are compared to ‘Control’ in which airflow is unidirectional (no reversal). It has been found that, for the moisture content distribution, the first reversal is critical and frequencies of subsequent flow reversals can be varied depending on the drying temperature used. However, more frequent airflow reversal has benefits in reducing drying stresses. These findings are consistent with observations in commercial kiln drying of softwood lumber.